Occurrences and Functions of Ly6Chi and Ly6Clo Macrophages in Health and Disease - Li, Yuan-hui; Zhang, Yu; Pan, Gang; Xiang, Li-xin; Luo, Ding-cun; Shao, Jian-zhong (Frontiers in Immunology, 2022)
Macrophages originating from the yolk sac or bone marrow play essential roles in tissue homeostasis and disease. Bone marrow-derived monocytes differentiate into Ly6Chi and Ly6Clo macrophages according to the differential expression of the surface marker protein Ly6C. Ly6Chi and Ly6Clo cells possess diverse functions and transcriptional profiles and can accelerate the disease process or support tissue repair and reconstruction. In this review, we discuss the basic biology of Ly6Chi and Ly6Clo macrophages, including their origin, differentiation, and phenotypic switching, and the diverse functions of Ly6Chi and Ly6Clo macrophages in homeostasis and disease, including in injury, chronic inflammation, wound repair, autoimmune disease, and cancer. Furthermore, we clarify the differences between Ly6Chi and Ly6Clo macrophages and their connections with traditional M1 and M2 macrophages. We also summarize the limitations and perspectives for Ly6Chi and Ly6Clo macrophages. Overall, continued efforts to understand these cells may provide therapeutic approaches for disease treatment.